INTEGRASI SOSIAL DALAM MASYARAKAT MULTI ETNIK - Eka Hendry Ar. (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2013)
This is a social research focused on the processes of society integration in the period of post-conflict. Locus of research is in Kelambu, a village in Sambas Regency West Kalimantan Province in which in 1999 a bloody violence broken between ethnic groups living there. Applying sociological approach and the perspective of conflict study, it was revealed that so far community living in Sungai Kelambu village is in negative peace because negative effect of the last confict is still there.